Bringing Us Closer Together: The Influence of National Identity and Political Orientation on COVID-19-Related Behavioral Intentions - Simić, Andrej; Sacchi, Simona; Pagliaro, Stefano; Pacilli, Maria Giuseppina; Brambilla, Marco (Frontiers in Psychology, 2022)
A growing body of work has highlighted the importance of political beliefs and attitudes in predicting endorsement and engagement in prosocial behavior. Individuals with right-wing political orientation are less likely to behave prosocially than their left-wing counterparts due to high levels of Right-wing authoritarianism (RWA). Here, we aimed to extend prior work by studying how these political values relate to COVID-19 discretionary behaviors (i.e., prosocial and non-mandatory behaviors related to the control of the pandemic spread). Furthermore, we tested whether identification with the national group would influence the relationship between Right-wing authoritarianism and prosocial behavior. A cross-sectional study conducted on 350 Italian participants showed that right-wing political orientation had a negative effect on COVID-19 discretionary behaviors via Right-wing authoritarianism. Furthermore, a moderated mediation model revealed that this effect was only significant for participants who are lowly identified with the national group. The results suggest that highlighting group belongingness might effectively motivate more conservative individuals to engage in prosocial behavior.